2020
DOI: 10.1519/jsc.0000000000003809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-Alanine Supplementation on Monocyte Recruitment and Cognition During a 24-Hour Simulated Military Operation

Abstract: Wells, AJ, Varanoske, AN, Coker, NA, Kozlowski, GJ, Frosti, CL, Boffey, D, Harat, I, Jahani, S, Gepner, Y, and Hoffman, JR. Effect of β-alanine supplementation on monocyte recruitment and cognition during a 24-hour simulated military operation. J Strength Cond Res 34(11): 3042–3054, 2020—Sustained military operations (SUSOPs) result in psychological stress and cognitive dysfunction, which may be related to the recruitment of classical monocytes into the brain. This study examined the effect of beta-alanine (BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Two studies showed that changes in reaction time favored placebo compared with a beta-alanine condition to a small extent (−0.30 [−1.27, 0.66]) [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies showed that changes in reaction time favored placebo compared with a beta-alanine condition to a small extent (−0.30 [−1.27, 0.66]) [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two military studies were subgrouped to examine the effect of beta-alanine on reaction time [ 61 , 62 ] Wells et al [ 61 ] randomly assigned 19 soldiers to groups of 12 g per day beta-alanine ( n = 10) or placebo ( n = 9) for 14 days before assessing performance in the Automated Neuropsychological Assessment Metrics (ANAM) during a 24 h sustained operations protocol. The ANAM is a clinically validated cognitive assessment tool, measuring functions such as reaction time and mathematical abilities [ 66 ], although beta-alanine had no effect on any of the ANAM assessments [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations